Lopinavir dosing in HIV-infected children in the United Kingdom and Ireland. - Donegan, K; Doerholt, K; Judd, A; Lyall, H; Menson, E; Butler, K; Tookey, P; Riordan, A; Shingadia, D; Tudor-Williams, G; Gibb, D; Walker, A (2013)
BACKGROUND: Uncertainty surrounds the correct dosing of lopinavir/r (LPV/r) in HIV-infected children not receiving non-nucleoside reverse transcriptase inhibitors. The licensed total daily dose is 460 mg/m², whereas the original study, reporting excellent viral load (VL) suppression, used a higher 600 mg/m² dose. METHODS: We calculated LPV/r daily doses prescribed from 2000 to 2009 within the UK/Irish national Collaborative HIV Paediatric Study (CHIPS) cohort. Logistic and binomial mixed models were used to explore whether higher LPV/r doses affected VL suppression. RESULTS: Four hundred forty-four of 1201 (37%) children on antiretroviral therapy in CHIPS had taken lopinavir/r without non-nucleoside reverse transcriptase inhibitors. Of 1065 recorded doses, 48% were syrup, 27% capsules and 25% tablets. Ten percent of doses were >10% below 460 mg/m² per day, and 12% were >10% above 600 mg/m². In multivariable models, predictors of lower doses were: once versus twice daily dosing (32 mg/m² lower); syrup versus tablets/capsules (33 mg/m² lower); higher weight-for-age and height-for-age (24 mg/m² and 13 mg/m² lower per unit higher, respectively); and older age (13 mg/m lower per year older for those aged >10 years, P < 0.05). Dosing varied widely by hospital (P = 0.0004), with some targeting higher and others lower doses. For those receiving lopinavir/r for ≥6 months, there was a greater chance of VL <400 copies/mL with higher doses (odds ratio = 1.15 [95% confidence interval: 1.06-1.25 per 50 mg/m² higher], P = 0.001). CONCLUSIONS: Findings suggest substantial variation and large hospital-level effects in the LPV/r dose prescribed to HIV-infected children in the United Kingdom/Ireland. Higher doses appeared to improve long-term VL suppression, which may be critical in children who need life-long therapy. Results highlight the importance of optimizing dosing in HIV-infected children of all ages.